1992
DOI: 10.1042/bj2850839
|View full text |Cite
|
Sign up to set email alerts
|

Different culture methods lead to differences in glycosylation of a murine IgG monoclonal antibody

Abstract: A monoclonal IgG-1 was produced by culture of a murine hybridoma (3.8.6) by three different methods, namely culture in ascites, in serum-free media and in serum-supplemented media. IgG-1 was purified to homogeneity (as judged by SDS/PAGE under reducing conditions) from each medium by ion-exchange chromatography and h.p.l.c. Protein A chromatography. Oligosaccharides were released from each IgG-1 preparation by hydrazinolysis and radiolabelled by reduction with alkaline sodium borotritide, and 'profile' analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(62 citation statements)
references
References 21 publications
5
57
0
Order By: Relevance
“…Therefore, except for the sialylation degree, EPO glycosylation was not significantly modified by the serum removal from the culture medium, which suggests that the intracellular process of EPO glycosylation involving numerous glycosyltransferases and glycan precursors seems to be not compromised. This phenomenon was already reported in the literature as serum was shown to affect the sugar content of the glycans of glycoproteins, particularly by decreasing the sialylation degree which is known to play a critical role in their biological activity (Patel et al 1992;Megaw and Johnson 1979;Maiorella et al 1993;Lamotte 1997;Gawlitzek et al 1995). However, these results seem to be closely dependent on the molecule investigated and of the culture conditions used (Gawlitzek et al 1995) as other papers reported a minor effect of the serum on the glycosylation pattern of recombinant proteins (Lifely et al 1995;Moellering et al 1990;Kopp et al 1996).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Therefore, except for the sialylation degree, EPO glycosylation was not significantly modified by the serum removal from the culture medium, which suggests that the intracellular process of EPO glycosylation involving numerous glycosyltransferases and glycan precursors seems to be not compromised. This phenomenon was already reported in the literature as serum was shown to affect the sugar content of the glycans of glycoproteins, particularly by decreasing the sialylation degree which is known to play a critical role in their biological activity (Patel et al 1992;Megaw and Johnson 1979;Maiorella et al 1993;Lamotte 1997;Gawlitzek et al 1995). However, these results seem to be closely dependent on the molecule investigated and of the culture conditions used (Gawlitzek et al 1995) as other papers reported a minor effect of the serum on the glycosylation pattern of recombinant proteins (Lifely et al 1995;Moellering et al 1990;Kopp et al 1996).…”
Section: Discussionsupporting
confidence: 58%
“…Thus, the sialic acid content of a monoclonal IgG 1 produced by murine hybridoma was reported to be clearly higher in serum-free medium than in presence of serum (Patel et al 1992) while Lifely et al (1995) observed only minor differences in glycosylation of an antibody produced by CHO cells in serum-free and serumcontaining media. Moellering et al (1990) did not find any significant differences in carbohydrate composition of another monoclonal antibody produced in both conditions.…”
Section: Introductionmentioning
confidence: 96%
“…In early years the MABs were deglycosylated and analyzed with, e.g., 1 H NMR [10], sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) [11], hydrophobic interaction chromatography [11], and high-pH anion-exchange chromatography with pulsed amperometric detection (HPAEC-PAD) [12]. Radio labeling of the released glycans, and analyzing them by a combination of paper electrophoresis and gel-filtration chromatography [13], with normal phase high-performance liquid chromatography (HPLC) [14,15] or anion-exchange HPLC [16] coupled with a fluorescence detector have also been described. Additionally, capillary electrophoresis coupled with different detectors has been described [17][18][19].…”
mentioning
confidence: 99%
“…Once secreted, solubility, aggregation, stability and immunogenicity of the protein may be affected by its glycosylation pattern (Kobata 1992;Sinclair and Elliott 2005;Willey 1999;Wyss and Wagner 1996). N-glycosylation is initiated in the ER, and O-glycosylation can be initiated in either the ER or Golgi apparatus, but due to processing inconstancies glycans can have frequent structural heterogeneities (Patel et al 1992;Seth et al 2006a;Varki 1998). The most common therapeutic monoclonal antibody approved biopharmaceutical is of the immunoglobulin G (IgG) class (Walsh and Jefferis 2006).…”
Section: Optimisation Of Glycosylation Patternsmentioning
confidence: 99%
“…The most common therapeutic monoclonal antibody approved biopharmaceutical is of the immunoglobulin G (IgG) class (Walsh and Jefferis 2006). This glycoprotein has several isoforms which are cell line and clone dependent, plus the structure is influenced by the culture environment (Chee Furng et al 2005;Patel et al 1992;Raju et al 2000). This structure or the pattern of glycosylation is dependent on the glycosyltransferases present in the Golgi apparatus.…”
Section: Optimisation Of Glycosylation Patternsmentioning
confidence: 99%